Гонения на генетику в русской прозе второй половины XX века - Попович, Наталья (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Lysenkoism was a political campaign against genetics and science-based agriculture conducted by Trofim Lysenko, his followers and Soviet authorities. Many books on this theme were forbidden in Russia and published abroad. Novel The White Robes by Dudintsev is a fictionalized version of the devastation, which Lysenko wreaked on Soviet genetic study. Novels Nikolai Nikolaevich by Aleshkovsky and The Life and Extraordinary Adventures of Private Ivan Chonkin by Voinovich describe the topic in a satirical style. The actuality of the theme is confirmed by its presence in Russian mass media in the form of materials aimed at justifying Lysenko's activity in the recent years.